Accommodations Knowledge and Practice for Students With Visual Impairments. (November 2021) - Nannemann, Allison C.
Introduction: Classroom accommodations are a primary means of supporting the appropriate education for students with disabilities. Student involvement in the accommodation process is valuable. Therefore, we need to teach students to be knowledgeable and strategic regarding their accommodations. Methods: Four high school students with visual impairments were taught the Student Self-Accommodation Strategy (SSA). A comparative case studies approach within a sequential explanatory design was used to investigate their accommodations knowledge and practices. Results: Participants improved or maintained accommodations knowledge. Their most-used types of accommodations were access accommodations and accommodations for content support. Three of the participants increased advocacy after strategy instruction. The participants' accommodation practices were influenced by emotional-behavioral regulation, independence, and teacher involvement. Discussion: Findings from this study relate to existing literature on accommodations support, teacher involvement in the accommodations process, instruction in accommodations advocacy, and the relationship between accommodations and emotional-behavioral dysregulation. Implications: Findings emphasize the need to be explicit about the accommodations available to students with visual impairments and the need for strategy instruction in the SSA to address emotional-behavioral dysregulation.